In the House of Representatives, Watertown, August 10th, 1775, inasmuch as the time prefixed by the Continental Congress, prohibiting all exportation to Great-Britain, Ireland and the English West-India islands is not yet come . - Warren, James, 1726-1808 ([Printed by Benjamin Edes], 1775)
August 14, 1775 Resolutions by the Provincial Congress at Watertown which required all whaling ships to seek and obtain permission from the General Court of the colony.